Novel Roles of the Tim Family in Immune Regulation and Autoimmune Diseases - Liu, Yikai; Chen, Hongzhi; Chen, Zhiying; Qiu, Junlin; Pang, Haipeng; Zhou, Zhiguang (Frontiers in Immunology, 2021)
T cell Ig and mucin domain (Tim) protein family members were identified to be important regulators of the immune response. As their name indicates, Tim proteins were originally considered a T cell-specific markers, and they mainly regulate the responses of T helper cells. However, accumulating evidence indicates that Tims are also expressed on antigen-presenting cells (APCs), such as monocytes, macrophages, dendritic cells (DCs) and B cells, and even plays various roles in natural killer cells (NKs) and mast cells. In recent years, the expression and function of Tims on different cells and the identification of new ligands for the Tim family have suggested that the Tim family plays a crucial role in immune regulation. In addition, the relationship between Tim family gene polymorphisms and susceptibility to several autoimmune diseases has expanded our knowledge of the role of Tim proteins in immune regulation. In this review, we discuss how the Tim family affects immunomodulatory function and the potential role of the Tim family in typical autoimmune diseases, including multiple sclerosis (MS), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and type 1 diabetes (T1D). A deeper understanding of the immunoregulatory mechanism of the Tim family might provide new insights into the clinical diagnosis and treatment of autoimmune diseases.